Cyclodextrin‐Assisted Delivery of Azobenzene Photoswitches for Uniform and Long‐Term Restoration of Light Responses in Degenerated Retinas of Blind Mice. Issue 9 (22nd July 2021) - Cao, Kevin J.; Lyons, Elijah F.; Smith, Benjamin E.; Denlinger, Bristol L.; Ma, Hong; Shirian, Jonathan D.; Kramer, Richard H.
Abstract: Azobenzene photoswitches are promising drug candidates for bestowing light sensitivity onto retinal neurons after photoreceptors degenerate in blinding disorders such as retinitis pigmentosa (RP). A potent photoswitch, BENAQ, targets a subset of retinal ganglion cells (RGCs), interacting with voltage‐gated ion channels to enable light‐triggered action potential firing. In mouse models of RP, injection of BENAQ into the vitreous of the eye photosensitizes RGCs to non‐damaging wavelengths and intensities of light. While the concentration required to elicit light responses is non‐toxic, effective drug delivery to the retina in vivo has remained a serious challenge. BENAQ aggregates near the injection site, causing non‐uniform photosensitization with a half‐life of 7 days, too transient for therapeutic vision restoration. Here, cyclodextrins are used to encapsulate BENAQ via host–guest chemistry to increase solubility and improve retinal delivery. SBE‐CD, a sulfobutylether β‐cyclodextrin, envelops the aromatic moieties of BENAQ to form a stable complex that dramatically enhances photosensitization, prolonging light responses to a half‐life of 31 days. SBE‐CD also ensures dispersal of BENAQ, resulting in uniform photosensitization across the retina. Hence the host–guest interaction between SBE‐CD and BENAQ overcomes limitations of intraocular delivery, guiding how photoswitches may be formulated as a possible treatment for human blindness. Abstract : BENAQ, an azobenzene photoswitch, imparts light sensitivity onto ordinarily light‐insensitive neurons. It is a promising vision‐restoring therapeutic for treating blindness, but because of self‐aggregation, drug delivery is a serious challenge. A modified β‐cyclodextrin, SBE‐CD, undergoes host–guest chemistry with BENAQ, dispersing it across the retina and slowing its release to enable uniform photosensitization that persists for >2.5 months in vivo.